Zindiqs and Sinners in the 17th Century: Examples from Record Books of Complaints - Ursinus, Michael; Weineck, Benjamin (Journal of Alevism-Bektashism Studies, 2022)
This article addresses the problem of Alevi history in the 17th century, as this period remains one of the severest lacunae in research on Alevism up until now. It is widely assumed that Alevis had withdrawn from the historical scene during this period, avoiding any contact with the Ottoman state and its local powerbrokers. Based on an Ottoman register of complaints (şikayet defteri) from 1675 the authors propose a philological framework that helps reconstruct Alevi social and religious history through the bits of information provided in such texts.
Keywords: Alevis; şikayet defteri; 1675; Anatolia; rafızi; tekke